Penerapan Metode MVC Framework Code Igniter untuk Sistem Informasi Administrasi Transaksi E-Commerce Perusahaan Aktualita - Usna, Sunarto; Yanto, Andri; Soegijanto, Soegijanto (Jurnal Informatika Universitas Pamulang, 2021)
Aktualita is one of the business activities engaged in the sale of stationery and printing located in South Jakarta. Activities related to promotions, data collection of goods, processing carried out do not yet have a standard database. Data processing takes a long time to produce information. The processing process contains errors in recording inaccurate data. Based on this information, the researchers tried to make a solution to these problems by creating a system in the form of a website using the CodeIgniter Framework. This research activity intends to find a solution with an administrative system for managing sales of goods transactions. The system built in this study uses a codeigniter framework. Making sales applications can be a solution to help make it easier for companies to actually manage goods data. Good data processing can make it easier to generate reports more quickly and accurately.